Research Institute of Education Science, Jeju National Universi 2020
DOI: 10.15564/jeju.2020.05.22.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Perception of middle school science teachers and students on the implementation of core ideas and science key competencies and emphasized in the 2015 revised curriculum

Abstract: On the basis of a second-year monitoring study on the implementation of the 2015 revised science curriculum this study examined how science teachers and students perceived the effectiveness of adapting core ideas and science key competencies. Data was collected by a survey questionnaire and interviews. In results, first, the teachers positively evaluated the importance of addressing core ideas and science key competencies, but pointed out lack of in-service teacher training and instructional supports and lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To understand these challenges, there have been several studies examining the suitability of the 2015 national science curriculum. Lee et al (2020) found that while the curriculum did not change significantly in terms of form and content, the inquiry activities designed to cultivate competencies were not being well performed in the field. Jeong (2020) noticed difficulties faced by teachers in inquiry classes caused by the changes requiring teachers to utilize new technologies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…To understand these challenges, there have been several studies examining the suitability of the 2015 national science curriculum. Lee et al (2020) found that while the curriculum did not change significantly in terms of form and content, the inquiry activities designed to cultivate competencies were not being well performed in the field. Jeong (2020) noticed difficulties faced by teachers in inquiry classes caused by the changes requiring teachers to utilize new technologies.…”
Section: Introductionmentioning
confidence: 94%
“…While the majority of teachers thought the amount was appropriate, considerable opinions were that it was insufficient or excessive. These responses indicate that not all teachers are sufficiently reflecting the intent of the curriculum in their classes (Lee et al, 2020;Kim & Na, 2017). This was also pointed out by teachers who felt that for all students to have access to a similar quality of inquiry activities, teachers needed support to faithfully guide students.…”
Section: Suggestions For Supporting Inquiry That Is Difficult Formentioning
confidence: 99%